Parameters That Influence Corrosion Detection in Reinforced Concrete Based on Eddy Current Thermography - Lu Liu; Dan Zheng; Jianting Zhou; Juan Yang; Hong Zhang (Advances in Civil Engineering)
This study introduces an eddy current thermography technique that can be used to detect and evaluate steel corrosion in a reinforced concrete structure. The rate of surface temperature changes in reinforced concrete is proposed as a means to characterize the degree of steel bar corrosion. The rate of surface temperature changes increased gradually with an increase in the corrosion degree. The influence of structural parameters on the rate of the temperature change was analyzed in detail. The results indicated that the rate of surface temperature change increased with a decrease in the concrete cover depth and with an increase in the humidity of the concrete, and this was affected by the diameter of the internal steel bar. Concrete cover was the most significant factor that affected the rate of the surface temperature change, except for the corrosion degree. The variations in the surface temperature of reinforced concrete can be explained using the law of electromagnetic induction and the electrochemical property change of corroded steel bar. This research provides a reliable basis for real-world applications and is helpful to understand the application scope of eddy current thermography technology for the quantitative detection of steel corrosion.